Tangential Intrahypothalamic Migration of the Mouse Ventral Premamillary Nucleus and Fgf8 Signaling - López-González, Lara; Alonso, Antonia; García-Calero, Elena; de Puelles, Eduardo; Puelles, Luis (Frontiers in Cell and Developmental Biology, 2021)
The tuberal hypothalamic ventral premamillary nucleus (VPM) described in mammals links olfactory and metabolic cues with mating behavior and is involved in the onset of puberty. We offer here descriptive and experimental evidence on a migratory phase in the development of this structure in mice at E12.5-E13.5. Its cells originate at the retromamillary area (RM) and then migrate tangentially rostralward, eschewing the mamillary body, and crossing the molecularly distinct perimamillary band, until they reach a definitive relatively superficial ventral tuberal location. Corroborating recent transcriptomic studies reporting a variety of adult glutamatergic cell types in the VPM, and different projections in the adult, we found that part of this populational heterogeneity emerges already early in development, during tangential migration, in the form of differential gene expression properties of at least 2-3 mixed populations possibly derived from subtly different parts of the RM. These partly distribute differentially in the core and shell parts of the final VPM. Since there is a neighboring acroterminal source of FGF8, and Fgfr2 is expressed at the early RM, we evaluated a possible influence of FGF8 signal on VPM development using hypomorphic Fgf8neo/null embryos. These results suggested a trophic role of FGF8 on RM and all cells migrating tangentially out of this area (VPM and the subthalamic nucleus), leading in hypomorphs to reduced cellularity after E15.5 without alteration of the migrations proper.